NEKROLISIS EPIDERMAL TOKSIK (NET) YANG DICURIGAI KARENA OBAT PELANGSING: Laporan satu kasus - Anjayani, Sukma Cukey; Shaleh Mathar, Nur Rahmah (Journal Medical Universitas muhammadiyah Makassar, 2023)
Toxic Epidermal Necrolysis is a rare life-threatening skin disorder, with severe loss of epidermis and mucous membrane involvement. Most often caused by secondary drug use. A case of toxic epidermal necrolysis in 29 years 29-year-old woman. Probable was caused by a slimming drug. The treatment was a systemic corticosteroid. The treatment gives an improvement.